Pengaruh Self Efficacy terhadap Hasil Belajar Matematika Siswa - Ika Laila; Feronika Sani Susanti Sinaga; Lilis Saputri (UIR Press, 2026)
Self-efficacy is thought to be an internal factor that can influence student performance, as it relates to a person's belief in their own abilities. This study aims to analyze the effect of self-efficacy on the mathematics learning outcomes of 10th grade students at Stabat 1 Public High School and to identify the level of this relationship. This study uses a quantitative method. The population in this study was all 360 10th grade students at Stabat 1 Public High School. The sampling technique used simple random sampling, and the sample for this study consisted of 35 tenth-grade students. Data collection was conducted through a self-efficacy questionnaire and documentation of mathematics learning outcomes. Data analysis used simple linear regression testing through prerequisite tests in the form of normality and linearity tests. The results showed that the data were normally distributed and had a linear relationship between the two variables. The calculated F value was 7.762 with a significance of 0.009 (< 0.05), indicating a significant effect between self-efficacy and mathematics learning outcomes. However, the regression coefficient of -1.348 showed a negative effect, meaning that an increase in self-efficacy was not always followed by an increase in learning outcomes. Meanwhile, the relationship between self-efficacy and learning outcomes was in the moderate category. Thus, students' self-efficacy is still insufficient to guide their learning habits. In order to achieve optimal learning outcomes, self-efficacy needs to be accompanied by the development of academic abilities and effective learning strategies.